Aktywność matematyczna w procesie dziecięcego konstruowania – zgodnie z koncepcją Seymoura Paperta - Brudzińska, Patrycja (Studia Edukacyjne, 2025)
The article presents the results of qualitative research aimed at identifying the mathematical activities undertaken by students during their engagement in the construction process. Two main research questions were highlighted: What attitude do first-grade students adopt towards mathematical problemsolving tasks during their involvement in productive activities? How does the process of investigation and experimentation unfold during construction? The qualitative analysis employed thematic coding and categorization. In the first part of the text, I discuss issues related to the concept of constructiotism. In the second part, I present the research conclusions. Productive activity can stimulate heuristic thinking of an operational nature. During construction, children explore mathematical problems, attempt to solve them, and create their own action strategies.